2001
DOI: 10.2134/agronj2001.932435x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Nitrogen Application Timing in No‐Till Soft Red Winter Wheat

Abstract: resulted in the highest yields in these fields. Nitrogen applications at GS-25 can stimulate tiller development As no-till acreage increases, N management guidelines need rein southeastern wheat production because winter wheat examination due to the potential effects of surface residue on N transformations and crop development. Our objectives were to deter-does not enter a dormant state in these southern latmine: (i) if N applied at Zadok's Growth Stage (GS) 25 improves itudes. grain yield of no-till winter wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 13 publications
1
73
3
Order By: Relevance
“…Trials were conducted on a Johns sandy loam in 2013-2014, with very low organic matter (12 g kg -1 ) compared to the Portsmouth sandy loam (120 g kg -1 ) utilized the following year. Grain yield did not reach a plateau within the range of included N rates in either year, and although there was evidence of continued yield response at the 180 kg N ha -1 application rate, the average total N application rate for wheat falls near the North Carolina recommended rate of 134 kg N ha -1 ; Weisz et al, 2001), with the risks of lodging increasing greatly beyond this rate Alley et al, 1996;Weisz, 2015). At the piedmont sites, grain yields between years were only significantly different at the 90 kg N ha -1 rate (Fig.…”
Section: Wheatmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials were conducted on a Johns sandy loam in 2013-2014, with very low organic matter (12 g kg -1 ) compared to the Portsmouth sandy loam (120 g kg -1 ) utilized the following year. Grain yield did not reach a plateau within the range of included N rates in either year, and although there was evidence of continued yield response at the 180 kg N ha -1 application rate, the average total N application rate for wheat falls near the North Carolina recommended rate of 134 kg N ha -1 ; Weisz et al, 2001), with the risks of lodging increasing greatly beyond this rate Alley et al, 1996;Weisz, 2015). At the piedmont sites, grain yields between years were only significantly different at the 90 kg N ha -1 rate (Fig.…”
Section: Wheatmentioning
confidence: 99%
“…The atplant N application rate for wheat was 34 kg N ha -1 followed by 0,45,90,135,180 kg N ha -1 as spring applied N prior to formation of the first joint (Feekes stage 4-5 or Zadoks stage 30; Weisz et al, 2001); thus there was no true zero-N application. At-plant N was applied as UAN and spring N was applied as UAN or UAN treated with NBPT+DCD, Nitrapyrin, or an organo-Ca.…”
Section: Field Studymentioning
confidence: 99%
“…It is possible that tiller densities in this study were not low enough to produce the measurable yield differences between the PP L + T1 39 and PP L + T2 39 applications that others have found. For instance, in a study with non-organically managed no-till winter wheat, Weisz et al [48] showed that when tiller densities were below 550 tillers m −2 , treatments with supplemental N applied at GS25 and split applied between GS25 and GS30 produced greater yields than the treatment with supplemental N at GS30. Therefore, fully evaluating topdressing timing effects at the threshold established by Scharf and Alley [47] was limited by the fact that tiller densities at most site-years were adequate but never well below the threshold (738, 906, and 890 tillers m −2 in ME-2013, VT-2012, and VT-2013, respectively) and exceeded 1000 tillers m −2 in just ME-2012 (1371 tillers m −2 ).…”
Section: In-season Test: Tiller Densitymentioning
confidence: 99%
“…The PP-only treatments did not produce statistically different tiller densities and an effort to capture a wider range through seeding rates and dates may be needed. For instance, Weisz et al [48] found that different seeding rates and dates produced a range of 162 to 1774 tillers m −2 in soft red winter wheat.…”
Section: In-season Test: Tiller Densitymentioning
confidence: 99%
“…Research in precision farming has been more and more focused on nitrogen application rates during growing stages for high yield and quality, and for environmental pollution control [29,38,42]. Under normal conditions, nitrogen fertilizer influences nitrogen concentration and color in green leaf, which are related to photosynthetic pigment contents and photosynthesis rates.…”
Section: Introductionmentioning
confidence: 99%